Oxygen Scavenging Effect of LaLuO3/TiN Gate Stack in High-Mobility Si/SiGe/SOI Quantum-Well Transistors - 冯锦锋 刘畅 俞文杰 彭颖红 (中国物理快报：英文版, 2016)
Higher-s dielectric LaLuO3, deposited by molecular beam deposition, with TiN as gate stack is integrated into high-mobility Si/SiGe/SOI quantum-well p-type metal-oxide-semiconduetor field effect transistors. Threshold voltage shift and capacitance equivalent thickness shrink are observed, resulting from oxygen scavenging effect in LaLuO3 with ti-rich TiN after high temperature annealing. The mechanism of oxygen scavenging and its potential for resistive memory applications are analyzed and discussed.